Carbon stock analysis of some cocoa planting systems in climate change mitigation efforts in East Luwu Regency. Issue 1 (April 2020) - Faradilla, L; Mustari, K; Asrul, L; Kaimuddin,
Abstract: Global warming is very closely related to carbon stored in an ecosystem. This research aimed to determine the amount of carbon storage in cocoa plantations in East Luwu Regency. The research was carried out in cacao plantation in three districts namely Burau, Wotu and Mangkutana. Measurement of carbon storage was conducted using the allometric formula on an observation plot of 200 m 2 . Six sampling points were selected consisted of four location with shading trees planted in multistrata agroforestry planting system and two locations with a monoculture planting system. The results of measurements on cocoa plants show that carbon storage increased with the variety of plant species that exist in the cocoa farm. The size of the carbon stocks depends on the planting system. Cacao plantation with multistrata shades system showed carbon absorption of 148.92 tons/Ha that was greater than the amount of carbon absorption in cocoa plantation with monoculture shades system of 50.24 tons/Ha. The level of carbon uptake in East Luwu Regency is 33.19 tons C/Ha. The amount of carbon emissions absorbed is 57.46 t/Ha. CO2 content with the composition of existing land cover in East Luwu Regency is 121.81 tons CO2 /Ha.